Aspectos contables de las criptomonedas, sus riesgos y regulación - Chavez Pinzon, Leidy Dayana (Universidad Antonio Nariño, 2023)
The present work is done in order to know the accounting aspects that cryptocurrencies have, the risks that these present and what type of regulations they have in Colombia and in other countries, cryptocurrencies are an electronic means to make transactions and investments quickly and effectively, however the use of these has several implications since they are not regulated in much of the world, some of these implications are the fluctuation of their value, are difficult to trace; thanks to this, several authors mention that this type of coin can be used to commit terrorist acts, extortion and the financing of illegal acts.. The regulation of cryptocurrencies is very important because you can have some parameters to protect users' money and reduce illegal acts; by comparing regulations from different countries you can come to better draft laws to have better restrictions on the use of cryptocurrencies.